PENGAJARAN BAHASA INDONESIA DI PERGURUAN TINGGI KEAGAMAAN ISLAM NEGERI (PTKIN) - Mu'awanah, Uyu; Marini, Arita; Maksum, Arifin (Al Qalam, 2020)
Indonesian society has a diversity of social, cultural, political aspirations, and economic capabilities. This diversity directly affects the ability of lecturers to carry out teaching, the ability of universities to provide lecture experiences, and the ability of students to process lectures and process information into something that can be translated as a result of lectures. This diversity becomes an independent variable that has a significant contribution to the success of lectures in Indonesian language education both as a process and as a result. Therefore, this diversity must be a factor that is taken into account and taken into account in determining the teaching of the Indonesian language which is not only in the form of linguistic rules and psychological aspects, but also the cultural aspects of the Indonesian people who are the largest community in Southeast Asia.